2019
DOI: 10.1111/jbi.13517
|View full text |Cite
|
Sign up to set email alerts
|

Diatom β‐diversity in streams increases with spatial scale and decreases with nutrient enrichment across regional to sub‐continental scales

Abstract: Aim To quantify the relative contributions of local community assembly processes versus γ‐diversity to β‐diversity, and to assess how spatial scale and anthropogenic disturbance (i.e. nutrient enrichment) interact to dictate which driver dominates. Location France and the United States. Time period 1993–2011. Major taxa studied Freshwater stream diatoms. Methods β‐diversity along a nutrient enrichment gradient was examined across multiple spatial scales. β‐diversity was estimated using multi‐site Sørensen diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…pH, alkalinity, nutrients), providing additional important influences on the richness and composition of diatom assemblages (Douglas & Smol, 2010; Michelutti, Douglas, & Smol, 2006; Passy et al, 2018; Smol & Douglas, 2007a; Wolfe, 2002). It is likely that diatom richness in circum‐Arctic streams is influenced by similar factors as in lakes, but stream system studies are less common (but see Leboucher et al, 2019; Pajunen, Luoto, & Soininen, 2016). In a recent study using data from stream localities in the U.S.A. and Finland, Passy et al (2018) showed that a decline in diatom species richness with increasing latitude could be coupled to decreasing temperature and nutrients (total phosphorus concentrations), suggesting that factors other than climate are also important drivers of species richness in high latitude regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pH, alkalinity, nutrients), providing additional important influences on the richness and composition of diatom assemblages (Douglas & Smol, 2010; Michelutti, Douglas, & Smol, 2006; Passy et al, 2018; Smol & Douglas, 2007a; Wolfe, 2002). It is likely that diatom richness in circum‐Arctic streams is influenced by similar factors as in lakes, but stream system studies are less common (but see Leboucher et al, 2019; Pajunen, Luoto, & Soininen, 2016). In a recent study using data from stream localities in the U.S.A. and Finland, Passy et al (2018) showed that a decline in diatom species richness with increasing latitude could be coupled to decreasing temperature and nutrients (total phosphorus concentrations), suggesting that factors other than climate are also important drivers of species richness in high latitude regions.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that diatom richness in circum-Arctic streams is influenced by similar factors as in lakes, but stream system studies are less common (but see Leboucher et al, 2019;Pajunen, Luoto, & Soininen, 2016). In a recent study using data from stream localities in the U.S. A.…”
Section: Full Core Analyses: Diatom β-Diversity (Species Turnover) Te...mentioning
confidence: 99%
“…the regional species pool) diversities (Whittaker, 1960; Whittaker, 1972). During the past several decades, researchers have paid considerable attention to beta diversity (Anderson et al, 2011; Leboucher et al, 2019). However, a common limitation of those investigations is that community information was often collected from a single date (Heino et al, 2015; Sinclair et al, 2021), either because of the complications involved in sampling across seasons or due to the study objective that did not consider temporal variation.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are thus consistent with Goldenberg Vilar et al (2014), who concluded that in high productivity environments the mass effect process seems to play a prominent role in structuring diatom communities. More generally, previous studies suggested that nutrient enrichment weakened the influence of species sorting in favour of mass effect, which became a more important driver of community composition (Leboucher et al., 2019). This may also explain the basin‐specific differences in the group assignments of the species.…”
Section: Discussionmentioning
confidence: 99%
“…We tested our approach on microscopic passive dispersers, stream diatoms, which are important primary producers in freshwater ecosystems (Likens, 1975; Potapova & Charles, 2002). Diatoms were shown to be structured by environmental filtering (Verleyen et al., 2009), dispersal (Göthe, Angeler, Gottschalk, Löfgren, & Sandin, 2013; Vanormelingen, Verleyen, & Vyverman, 2008; Vyverman et al., 2007) or both (Jamoneau et al., 2018; Leboucher et al., 2019; Soininen, Jamoneau, Rosebery, & Passy, 2016). In this respect, biovolumes and ecological guilds have been, in some studies, related to the strength of the spatial patterns (De Bie et al., 2012; Goldenberg Vilar et al, 2014; Heino & Soininen, 2006; Jamoneau et al., 2018), small organisms being more sensitive to dispersal‐driven processes and motile species being more strongly affected by mass effect.…”
Section: Introductionmentioning
confidence: 99%